Developmental changes in effective connectivity in the emerging core face network. - Cohen Kadosh, K; Cohen Kadosh, R; Dick, F; Johnson, M (2011)
Little is currently known about the postnatal emergence of functional cortical networks supporting complex perceptual and cognitive skills, such as face processing. The present study examined the emergence of the core cortical network underlying face processing in younger and older school-age children as well as young adults. Participants performed 3 functional magnetic resonance imaging target detection tasks where they either had to detect a specific facial identity, expression, or direction of eye gaze in a stream of consecutively presented faces. We compared the connectivity of the face network using dynamic causal modelling and observed that it emerges gradually during childhood. Further, we found that while the relative strength of functional network connections were differentially modulated by task demands in adults, there was no such modulation of this network in either older or younger children. These results were independent of the behavioral performance in the 3 age groups. We suggest that the emergence of the face network is due to continuous specialization and fine-tuning within the regions of this network. The current results have important implications for future studies investigating trajectories of brain development and cortical specialization both in typically and atypically developing populations.